At what age do normal weight Canadian children become overweight adults? Differences according to sex and metric - E. Barbour-Tuck; M. C. Erlandson; W. Johnson; N. Muhajarine; H. Foulds; A. D. G. Baxter-Jones (Taylor & Francis Group, 2018)
Background: The prevalence of overweight and obesity doubles between adolescence and young adulthood; however, the exact age, and appropriate metric to use to identify when overweight develops is still debated. Aim: To examine the age of onset of overweight by sex and four metrics: body mass index (BMI), fat mass (%FM), waist circumference (WC) and waist-to-height ratio (WHtR). Subjects and methods: Between 1991 and 2017, serial measures of body composition were taken on 237 (108 males) individuals (aged 8-40 years of age). Hierarchical random effects models were used to develop growth curves. Curves were compared to BMI, %FM and WC overweight age- and sex-specific cut-points. Results: In males, the BMI growth curve crossed the cut-point at 22.0 years, compared to 23.5 and 26.5 years for WHtR and %FM, respectively; WC cut-off was not reached until 36 years. In females, the BMI growth curve crossed the overweight cut-point at 21.5 years, compared to 14.2 years for %FM and 21.9 and 27.5 years for WC and WHtR, respectively. Conclusion: In summary, overweight onset occurs during young adulthood with the exception of WC in males. BMI in males and %FM in females were the metrics identifying overweight the earliest.